Proto-ubiquitin: A Bayesian prediction of an ancient protein during the prokaryotic-eukaryotic transition - Deocaris, Custer C. (Animo Repository, 2011)
Only recently have biologists been able to apply mathematical and biochemical tools to preview lifestyles of ancient life forms and "travel back in time." In this paper, we describe an ancestral reconstruction of ubiquitin to determine its molecular properties during the rise of the eukaryotes. Although ubiquitin is one of the most conserved proteins in eukaryotes, no ubiquitin homolog has been found in prokaryotic genomes sequenced thus far. In an attempt to derive the ancestral ubiquitin, or proto-ubiquitin (proto-Ub), we applied Bayesian statistical theory to estimate posterior probabilities of protein sequences from a minimum evolution tree of 30 extant species. The inferred ancestral sequence was 100% homologous with the ubiquitin of Brugia malayi, a parasitic nematode. Among its 76 amino acids, only nine residues have undergone amino acid modification. As no major structural and functional changes happened during the evolution of ubiquitin, we hypothesize that the stressful conditions that led to the creation of this gene after the "Great Oxidation Event" 2.4 billion years ago may have already been "buffered" to date.